2005
DOI: 10.1093/annonc/mdi901
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HER2 as a therapeutic strategy for breast cancer: a paradigmatic shift of drug development in oncology

Abstract: Targeted therapies are causing a dramatic change in cancer drug development. Trastuzumab, a humanized recombinant monoclonal antibody that recognizes the extracellular domain of HER2 trans-membrane protein, is among the first target-specific drugs that have been licensed for clinical use and its development represents a model of integration of new agents with classical treatment strategies. In preclinical models, trastuzumab has demonstrated a marked antiproliferative effect and a synergistic action with sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Based on the preliminary results from three available international studies [18], the Norwegian Breast Cancer Group (NBCG) has recommended trastuzumab as standard practice in adjuvant treatment of early breast cancer (www.nbcg.net). Employing our results, the coverage of trastuzumab in adjuvant setting can be justified on a cost-effectiveness basis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the preliminary results from three available international studies [18], the Norwegian Breast Cancer Group (NBCG) has recommended trastuzumab as standard practice in adjuvant treatment of early breast cancer (www.nbcg.net). Employing our results, the coverage of trastuzumab in adjuvant setting can be justified on a cost-effectiveness basis.…”
Section: Discussionmentioning
confidence: 99%
“…While there are several ongoing studies [18] in this setting, so far the results from four trials [12 Á14,19] have been reported in peer-reviewed journals. This include the international HERA trial [13] and the combined analysis of the two North American studies (National Surgical Adjuvant Breast and Bowl Project-NSABP B31 and North Central Cancer Treatment Group NCCTG N9831) [12].…”
Section: Effectivenessmentioning
confidence: 99%
“…1 However, when trastuzumab was used as a single agent for patients with Her-2/neu positive metastatic breast cancer, the response rate was found to be under 30%. 2,3 Therapeutic efficacy can be improved if the antibody is conjugated with cytotoxic agents and Her-2/neu overexpressing tumor cells are selectively targeted by trastuzumab-based immunoconjugates. 4,5 This approach, which can provide highly specific delivery of therapy and reduce host toxicity, presents a novel strategy for the treatment of breast as well as other epithelial cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The HER2 gene is amplified in 30% of invasive breast cancers and correlated with reduced patient survival [1]. Trastuzumab (Herceptin Ò ), a humanized monoclonal antibody which binds to the HER2 extracellular domain, deeply impacts on the treatment of breast cancers [2]. The HER2 gene is subjected to somatic mutations [3] and to germinal polymorphism.…”
mentioning
confidence: 99%